2021
DOI: 10.1162/jocn_a_01736
|View full text |Cite
|
Sign up to set email alerts
|

First and Second Language at Hand: A Chronometric Transcranial-Magnetic Stimulation Study on Semantic and Motor Resonance

Abstract: According to embodied theories, motor and language processing bidirectionally interact: Motor activation modulates behavior in lexico-semantic tasks (semantic resonance), whereas understanding motor-related words entails activation of the corresponding motor brain areas (motor resonance). Whereas many studies investigated such interaction in the first language (L1), only few did so in a second language (L2), focusing on motor resonance. Here, we directly compared L1 and a late L2, for the first time both in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 126 publications
(181 reference statements)
3
16
0
Order By: Relevance
“…Results revealed that semantic resonance occurred at early stages of semantic processing (TMS applied at 125 ms post-stimulus) for first-language words but not second-language words, while motor resonance induced by TMS occurred at slightly later stages of semantic processing (275 ms post-stimulus) for second-language words. These results support the notion that action and language interact at early stages of word processing, and first-language and second-language are differently embodied [86]. Nevertheless, studies show that children who acquire two languages from birth learn language in a manner comparable to monolingual children, whereas highly proficient late bilinguals seem to have a more grounded representation of their second language ([87] for a review).…”
Section: Plos Onesupporting
confidence: 81%
“…Results revealed that semantic resonance occurred at early stages of semantic processing (TMS applied at 125 ms post-stimulus) for first-language words but not second-language words, while motor resonance induced by TMS occurred at slightly later stages of semantic processing (275 ms post-stimulus) for second-language words. These results support the notion that action and language interact at early stages of word processing, and first-language and second-language are differently embodied [86]. Nevertheless, studies show that children who acquire two languages from birth learn language in a manner comparable to monolingual children, whereas highly proficient late bilinguals seem to have a more grounded representation of their second language ([87] for a review).…”
Section: Plos Onesupporting
confidence: 81%
“…For instance, the use of kinematic analysis to compare embodied effects across different languages (Gianelli et al, 2017), incorporating spatial and temporal precision to understand how embodied effects vary across different stages of lexical and semantic access. Additional insights may be gained by exploring linguistic-motor crosstalk in all aspects, such as the motor-semantic resonance (Monaco et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…One of these is the timing of embodiment effects and relative language implication. Following this recommendation, Monaco et al (2021) reported a difference in the motor language interaction between L1 and L2 at the early stages of word recognition.…”
Section: Crosslinguistic Differences and Effects Of L1 Vs L2mentioning
confidence: 97%
See 1 more Smart Citation
“…Compared to sham stimulation, verum stimulation slowed down the translation process for sensorimotor-enriched foreign words but not sensory-enriched foreign words. The specific influence of rTMS on the translation of sensorimotor foreign words suggested that M1 may be specifically implicated in the representation of these words (see also Tian et al, 2020 ; Monaco et al, 2021 , for similar results, and Adams, 2016 , for a review).…”
Section: Relationship Between the Motor And Language Systemmentioning
confidence: 90%